Relevance of Adult Literacy to National Development - (:unkn) unknown (My University, 2023)
The purpose of this research is to examine the relationship between adult literacy and national development. Literacy is an extensive skill that measures the education of a population as well as the gross per capita income. Literacy is a powerful tool and competence that extends beyond just reading and writing. As a powerful tool, it equips the individual for personal development. It is the foundation for any meaningful development of a nation. It is not a single entity but an interconnection of several fields-education, health, agriculture, and more. Today, within the context of globalization and technological competitiveness, the need for adult literacy is pertinent. Literate adults can be gainfully employed, thereby contributing to national development. However, not every adult is literate enough to qualify for employment that could lead to national development. Countries in sub-Saharan Africa have low literacy rates with gender and regional disparity. Thus, sub-Saharan African national governments need to step up the literacy apparatus of their countries for national development.
Keywords: African Research